TINGKAT PARTISIPASI PENGELOLAAN DAN ANALISIS FINANSIAL HUTAN RAKYAT DENGAN SISTEM TUNDA TEBANG DI KABUPATEN KONAWE SELATAN - La Ode Agus Salim Mando; Aminuddin Mane Kandari; Khairun Khairun; Rosmarlinasiah Rosmarlinasiah; Safril Kasim; La Ode Midi; Wa Ode Inda; Sitti Mardhatillah (Forestry Study Program University Of Mataram, 2020)
This study aims to determine the mechanism, level of participation, financial analysis in following the delayed logging program in community forests. The research was located in the community forests of Watudemba and Ulu Lakara villages, Konawe Selatan District from April to May 2018. Data collection techniques were carried out by observation, direct communication with 16 respondents and bibliographical studies. n addition, measurements were made by making 17 sample plots of teak stands (Tectona grandis L.f). The data analysis uses quantitative and qualitative methods. The results showed that: 1) The delay logging program mechanism consists of three stages, namely agreeing and signing a pending felling program agreement, distribution and loan repayment. 2) While the level of community participation in participating in the delayed cutting program at the planning stage (moderate-high, 81.25%), organizing (moderate-high, 68, 75%), implementation (moderate-high, 81.25%), as well as supervision and evaluation (moderate-high, 56.25%). 3) NPV value obtained is Rp. 266,811,200,-; BCR value obtained was 5.29; and the IRR value obtained by 37% over the age of the analysis of twenty years.